The dilemma of sustainability in the age of globalization : a quest for a paradigm of development - Bakari, Mohamed El-Kamel, 1972- (Globalization and its costs., 2017)
This book offers an exhaustive overview of the different political, social, and intellectual circumstances that paved the way for the inception of sustainable development. It offers in-depth analyses of economic globalization, current society-environment relationships, and global trade.